HUBUNGAN PENGETAHUAN GIZI, KONSUMSI PANGAN, AKTIVITAS FISIK DENGAN STATUS GIZI PADA SISWA SMP NEGERI 2 TANJUNG BALAI TAHUN 2016 - Retno Ayu Widya Cipta; Zulhaida Lubis; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
In adolescence often appear a variety of nutritional problems due to wrong nutrition behavior, namely the imbalance between nutritional intake with the recommended dietary allowance. Nutritional problems that can occur in adolescents is malnutrition and obesity. It can be influenced by knowledge of nutrition, food consumption, and physical activity. The aimed of research to determine the relationship between nutrition knowledge, food intake, and physical activity with nutritional status on student / i in SMP Negeri 2 Tanjungbalai. This type of research is descriptive observational with cross sectional design. The sample was 88 students by using proportional random sampling technique. Data were obtained through interviews using questionnaires, forms a 24-hour recall and food frequency question, and the measurement of height and weighing. Data analise using chi square test. The results showed that students who were normal nutritional status 54,5%, thin nutritional status of 12,5%, and the nutritional status of obese amounted to 33,0%. Students nutrition knowledge related to nutritional status (p = 0,013). Consumption of food which includes an arrangement of foods was not associated with nutritional status (p = 0,161), while the consumption of food that includes energy sufficiency level (p = 0,016), the adequacy of carbohydrates (p = 0,004), the adequacy of protein (p = 0,005), and the amount of fat (p = 0,018) associated with nutritional status. Students' physical activity associated with nutritional status (p = 0,024). Suggested to the school to add to the subject matter of nutrition, activate extracurricular activities for students through the School Health Unit to educate about nutrition, and doing activities more beneficial to the students as regular exercise in order to maintain health. Keywodrs: Nutrition Knowledge, Food Consumption, Physical Activity, Nutritional Status, Junior High School Students